2001
DOI: 10.1074/jbc.m108294200
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB1 (p50) Homodimers Contribute to Transcription of thebcl-2 Oncogene

Abstract: The bcl-2 proto-oncogene is frequently expressed in human cancer. Although bcl-2 was first cloned as the t(14;18) translocation breakpoint from human follicular B-cell lymphoma, it has become apparent that many cell types express bcl-2 because of transcriptional regulation. As such, several transcription factors have been demonstrated to activate expression of bcl-2, including NF-B. We investigated the role of NF-B1 (p50) homodimers in the expression of Bcl-2 in two murine B-cell lymphoma cell lines: LY-as, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
82
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(88 citation statements)
references
References 53 publications
5
82
1
Order By: Relevance
“…Our results indicate that NF-kB/Rel factors activate the bcl-2 promoter through interactions with the ATF/CREB and Sp1 factors and their binding sites rather than directly through a kB consensus sequence. This is in contrast to a recent study by Kurland and colleagues, which suggested that p50 homodimers activate bcl-2 expression by directly binding to kB sequences (Kurland et al, 2001). Moreover, one of the kB sequences that is inactive in t(14;18) cells was found to mediate positive regulation of bcl-2 P2 promoter activity in prostate carcinoma cells (Catz and Johnson, 2001).…”
Section: Discussioncontrasting
confidence: 54%
“…Our results indicate that NF-kB/Rel factors activate the bcl-2 promoter through interactions with the ATF/CREB and Sp1 factors and their binding sites rather than directly through a kB consensus sequence. This is in contrast to a recent study by Kurland and colleagues, which suggested that p50 homodimers activate bcl-2 expression by directly binding to kB sequences (Kurland et al, 2001). Moreover, one of the kB sequences that is inactive in t(14;18) cells was found to mediate positive regulation of bcl-2 P2 promoter activity in prostate carcinoma cells (Catz and Johnson, 2001).…”
Section: Discussioncontrasting
confidence: 54%
“…However, there are several reports that support the ability of p50/p50 homodimers to activate transcription (Dechend et al, 1999;Kurland et al, 2001;Priel et al, 2005). On the basis of our experiments with antisense oligonucleotides against p65 and p50, it is possible that p65/p50 heterodimers may also bind to a yet to be identified site of the let-7a-3/let7-cluster and activate its transcription.…”
Section: Discussionmentioning
confidence: 60%
“…In contrast, Bcl-2 has been found to be NF-κB dependent in many models (27)(28)(29), and the NF-κB inhibitor SN50 has been found to decrease levels of both Bcl-2 and cIAP-1, but not Mcl-1 (6). Others, however, have found that inhibition of NF-κB activity downregulates Bcl-2 in U266 but not in KMS-12PE multiple myeloma cells (13).…”
Section: Discussionmentioning
confidence: 93%
“…We further examined modulation of antiapoptotic and proapoptotic signaling pathways as previously reported to be affected by NF-κB inhibition in multiple myeloma. Bcl-2 has been found to be NF-κB dependent in many models (27)(28)(29), and the NF-κB inhibitor SN50 has been found to decrease levels of both Bcl-2 and cIAP-1 (6). We did not see changes in levels of Bcl-2 and cIAP1 (Fig.…”
Section: V1810-induced Apoptosis Is Associated With Proteasome-indepementioning
confidence: 99%